การคุ้มครองสิทธิเสรีภาพของคนต่างด้าวตามรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 : ศึกษากรณีสิทธิมนุษยชนกับสิทธิพลเมือง - ปิ่นธเนศ แก้วรุ่งฟ้า (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This thesis shall focus on studying protection of an alien’s rights and liberty of an alien by the provisions of the constitution because the Constitution of Kingdom of Thailand B.E. 2550 affirms the kinds of rights and liberty subject to the Section 3 "Rights and Liberty of Thai People" which are not categorized the rights and liberty separately between the provisions regarding affirmation of human rights and provisions regarding affirmation of civil rights which shall cause whether an alien can be a holder of the rights and liberty affirmed by the constitution or not and how? Moreover, we study the concepts and theories including the methods of protection of an alien’s rights and liberty by foreign constitutions in order to compare with the protection of rights and liberty of an alien according to the Constitution of Kingdom of Thailand B.E. 2550 so as to be a guideline for rectifying the form of affirmation of rights and liberty subject to the constitution in order to prevent some rights and liberty of such aliens including to find a method to create clarity and to consider easily that which parts of the provisions regarding affirmation of rights and liberty are the human rights or civil rights. Basically, if the kinds of rights and liberty which are categorized as the human rights, all people whether a citizen or an alien can be the holder of such human right, meanwhile the civil rights shall only be reserved for the citizen of such state who can be the holder of the civil right. From the research, it is found that the provisions affirming the rights and liberty subject to the Section 3 "The right and liberty of Thai people", the objective of the constitution does not focus on protecting right and liberty affirmed subject to such section to aliens but aliens’ rights and liberty are protected by article 4 affirmed in the Section 1 "General provisions" of the constitution affirming their rights and liberty broadly which cannot be stipulated descriptions clearly that such rights and liberty affirmed according to the article 4 whether what scope aliens shall be protected, because such rights and liberty affirmed according to the article 4 include human rights and civil rights together. Therefore, finally the consideration that how aliens shall be protected their rights and liberty according to the constitution, it shall have to always consider the subject matter of the rights and liberty as affirmed subject to the section 3. However, it lacks clarity that which article of section 3 aliens can be related to the rights and liberty in order to apply with article 4. Due to the fact that the provisions of section 3 are not vividly categorized between human rights on the one section and civil rights on the other section so that it can be understood that the provisions regarding human rights of aliens shall be protected by the constitution also. With regard to the provisions regarding civil rights, aliens cannot be protected by the constitution. Furthermore, the constitution affirms that "Person" who is the holder of a right in every article affirmed subject to the Section 3 can cause trouble to consider that which articles shall be the human rights or civil rights. Therefore, it is different from foreign constitutions affirming that an alien can be the holder of a right and liberty according to affirmation of such constitution, and it shall affirm that "Everyone" shall include the citizen of the state and aliens to be as the holder of a right for the articles affirming the human rights and it shall specifically affirm that ‘Citizen" to be the holder of a right in the article affirming the civil rights.In relation to such problem, the author has proposed the guideline of affirmation of the rights and liberty of an alien subject to the same section that the constitution affirms the right and liberty of Thai people. I have stipulated the title of the section widely that "Rights and Liberty" and divided the provisions subject to such section into 2 parts which are: the first part "Fundamental Rights and Liberty" in order to affirm the rights and liberty which are material shall be human rights and specified "Everyone" to be the holder of a right in every article affirming subject to the first part; and with regard to the civil rights, affirmed subject to the second part "Civil Rights" so as to specify "Thai People" to be the holder of a right in every article affirming subject to the second part in order to clearly stipulate the scope that an alien’s rights and liberty should be protected according to the constitution especially affirmed subject to the provisions of the first part "Fundamental Rights and Liberty" solely. Furthermore, to affirm the rights and liberty of an alien from the constitution level, it can be developed according to social variation and to solve the problems which may be incurred in the protection of an alien’s rights and liberty by the constitution, the author has proposed that the Constitutional Court shall be the main organization to solve such problems by means of having the Constitutional Court be the key role for creating the principles regarding the protection of rights and liberty which shall be equally enforced in the constitutional level which shall be the same as the Constitutional Court of France (La Conseil Constitutionel) creating the primary principles approved by the republic’ laws (Les principes fondamenteaux reconnus par les lois de la République) enacted to affirm the rights and liberty of aliens which is consistent with the social variation.